Applying Waterfall Method on Sales Information System - Veti Apriana; Sifa Fauziah (Institute of Computer Science (IOCS), 2021)
During the Pandemic, people's behavior in shopping experienced a significant change, from what people often shopped conventionally to shopping through e-commerce. With these conditions, business people must transform digitally to maintain their existence in their business. The decrease in direct contact with consumers leads to reduced sales and disrupted productivity problems. By using the waterfall method, the problem limitation in the sales information system process starts from the process of ordering goods, processing payments, the process of making reports and journals, starting from the login, main menu, transaction menu (sales of goods), and the report menu (reports of weekly and monthly sales of goods). With data processing using computerization, it is expected to help smooth sales data processing in providing fast, precise and accurate information and can be used for decision making.